Fractional Distillation in Natural Gas Liquid (NGL) Fractionation - Nnadikwe Johnson; Ezechukwu Chioma Mary-Jane; Samuel Kwelle; Okpala Blessing Chiamaka; Amaefula Chibunma Vivan; Momoh Abdulazeez Adeyemi (Journal Majelis Paspama, 2026)
Natural Gas Liquid fractionation is an energy-intensive process critical for producing high-purity ethane, propane, butane, and natural gasoline. Conventional 4-column fractionation trains operate with high reboiler and condenser duties, leading to increased operating costs and carbon emissions. This study presents the simulation, optimization, and energy analysis of a heat-integrated NGL fractionation process using Aspen HYS with Peng-Robinson equation of state. A base-case design was developed and validated against published plant data. Inter-column heat integration was implemented by using overhead vapor from the de-ethanizer to partially reboil the de-propanizer. Sensitivity analysis was conducted on reflux ratio, feed composition, and operating pressure to determine optimal operating conditions. Equipment sizing was performed using standard correlations from GPSA and Perry’s Handbook. of quantify heat recovery potential, a novel metric termed Thermal Coupling Index was introduced. Results show that the optimized design achieved 98.9% total NGL recovery with all products meeting GPA 2140 specifications. Total reboiler duty was reduced by 8.5%, and specific energy consumption decreased to 4.99 MM Btu/GPM, which is 11% lower than industry benchmarks. A TCI greater than 20% correlated with more than 6.8% energy savings, making it suitable for utility-limited and marginal field application.